Study on Emotions and Feelings in Early Childhood Education - Batista, Jéssica Bispo [UNESP]; Pasqualini, Juliana Campregher [UNESP]; Magalhães, Giselle Modé (FapUNIFESP (SciELO), 2022)
This study aimed to investigate the role of the pedagogical process on the development of emotions and feelings in the preschool age, based on the analysis of the child’s school activity. This research involved observa-tions in the classroom and an interview with the responsible teacher, in order to analyze the extent to which the pedagogical activities mobilized the emotional aspects of children and contributed to their affective-emotional development. The results showed that being recognized by the teacher in the collective is emotionally more significant than the nature and success of the task execution. It follows that understanding the dynamics of emotions in the concrete school life of pre-school children is essential for pedagogical planning that aim the emancipation of subjects.
Estudo sobre Emoções e Sentimentos na Educação Infantil.
Keywords: Cultural-Historical Psychology; Early Childhood Education; Emotions